2008
DOI: 10.2176/nmc.48.285
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Petit Mal-Like Seizure Induced by Microinjection of Kainic Acid Into the Unilateral Mediodorsal Nucleus of the Thalamus

Abstract: The mediodorsal nucleus (MD) of the thalamus has reciprocal projections with the frontal cortex and limbic system, and may be involved in absence seizures. Kainic acid was injected into the left MD of Wistar rats, and behavior and electroencephalography were monitored for 24 hours, then continued intermittently for 8 weeks. The rat brains were then examined histologically. Brain metabolic changes were also investigated by intravenous injection of 100 mCi/kg of [ 14 C]2-deoxyglucose to measure local cerebral gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…One of the major findings of this study was the delay in the first convulsive seizure after administering kainic acid in the GAERS rats compared with the Wistar rats; this finding corroborated our prior work (18). These studies suggest that although GAERS rats exhibited convulsive seizures and status epilepticus after the kainic acid administration, the time to the (12,19,30). The contralateral sides of the CA3, reticular nucleus, and the putamen were spared in the Wistar and GAERS rats.…”
Section: █ Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…One of the major findings of this study was the delay in the first convulsive seizure after administering kainic acid in the GAERS rats compared with the Wistar rats; this finding corroborated our prior work (18). These studies suggest that although GAERS rats exhibited convulsive seizures and status epilepticus after the kainic acid administration, the time to the (12,19,30). The contralateral sides of the CA3, reticular nucleus, and the putamen were spared in the Wistar and GAERS rats.…”
Section: █ Discussionsupporting
confidence: 88%
“…Moreover, the mediodorsal thalamic nucleus has been considered to play a role in absence seizures. Kato et al reported that the kainic acid administration into the mediodorsal thalamic nucleus triggered cognitive impairment and considered this region as the mechanism of petit mal seizures (19). Bertram et al reported that the mediodorsal thalamic nucleus plays a role in the limbic seizure circuit and the spread of seizures; the mediodorsal thalamic nucleus acts as a key control point of the seizure, which comes from limbic sites (6).…”
Section: █ Acknowledgmentsmentioning
confidence: 99%
“…Epilepsia ILAE tonic-clonic convulsions 27 as well as gelastic seizures in patients with hypothalamic hamartoma, 28 an epilepsy that often evolves to a Lennox-Gastaut phenotype. Furthermore, in rodent models of generalized absence epilepsy, kainic acid injections to the mediodorsal nucleus elicit slow spikeand-wave, 29 bilateral removal of the mediodorsal nucleus abolishes slow spike-and-wave, 30 and genetically predisposed strains develop spontaneous absence seizures that show early involvement of the ventrolateral thalamus. 31 Our findings in LGS show notable differences from previous observations in other generalized epilepsy syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this study further detected different morphological alterations of the thalamic nuclei in IGE-GTCS, specifically in the MDN and pulvinar nuclei. Previous animal experiment has suggested the MDN is involved in the mechanism of spike and wave complexes and propagation of seizure [19]. Hodaie and colleges have found bursting activity of neurons in MDN in epilepsy patients with generalized or second generalized seizure [20].…”
Section: Discussionmentioning
confidence: 99%